Is Preoperative Adrenal Insufficiency Screening Necessary for Cardiovascular Thoracic Surgery Patients? - Worapaka Manosroi; Pichitchai Atthakomol (Medicina, 2023)
Background: The association between adrenal insufficiency (AI) and the treatment outcomes of cardiothoracic surgery patients has been little reported. The aims of this study were to investigate the incidence of AI and to compare the post-surgical outcomes of patients with perioperatively treated AI and patients with a normal adrenal response. Methods: A 1.5-year prospective study was conducted in 98 patients scheduled for cardiothoracic surgery. Patients were categorized as either AI or normal-adrenal-response patients. Those with AI were treated with stress doses of glucocorticoid perioperatively. The post-surgical outcomes of patients with AI and of those with a normal adrenaline response were analyzed using multivariable analysis. Results: The overall incidence of AI was 34.7%. There were no statistically significant differences in post-surgical outcomes, including prolonged hospital stay, postoperative infection, prolonged inotropic drug use and relative AI, between the two groups. Only the rate of hyperglycemia requiring insulin infusion was significantly higher in the AI group than in the non-AI group (OR = 14.15, 95% CI = 1.44–138.60, p = 0.02). Conclusions: The proper diagnosis and management of AI can result in surgical outcomes in AI patients comparable to those of normal-adrenal-response patients. Non-life-threatening hyperglycemia requiring insulin infusion was found only in the AI group.